Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2019)
Urochordeumatidae Silvestri, 1909 includes a single species, Urochordeuma bumpusi Silvestri, 1909, with U. porona Chamberlin, 1941 as a new junior subjective synonym. The family Urochordeumatidae is removed from the superfamily Caseyoidea and transferred to the superfamily Striarioidea. The species is known only from four counties in Washington State in the North Cascades: Pierce, King, Thurston and Whatcom. The occurrence of U. bumpusi from Whatcom County is a significant range extension.